2013
DOI: 10.1159/000351133
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interactions with Anticancer Agents: A Cross-Sectional Study

Abstract: Background: Patients with cancer are particularly susceptible to drug interactions (DIs), but the extent of the problem has received limited attention. We aimed to evaluate the frequency of interactions with anticancer agents in a group of cancer patients. Methods: The study was performed in a Belgian teaching hospital. One hundred and twenty-two patients with solid malignancies were included. A comprehensive drug history was performed by a clinical pharmacist. Three renowned DI compendia were used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 68 publications
3
18
1
Order By: Relevance
“…Chemoprevention may not be possible by application of single agents and so compounds having pleiotropic actions are often recommended but studies with garlic (Allium sativum), ginkgo (Ginkgo biloba), echinacea (Echinacea purpurea), ginseng (Panax ginseng), St John' s wort (Hypericum perforatum), and kava (Piper methysticum) show undesired effects in cancer treatment. These phytochemicals interact with drug transporter P-gp, and other oxidative enzymes leading to phytokinetic alteration of commonly used chemotherapeutic drugs like cisplatin and methotrexate resulting in their low absorption and high elimination [24]. Such unfavorable drug interactions can do more evil than good in cancer patients stipulating more focus to be directed in unraveling the molecular mechanisms imparted by a phytochemical before being used in alliance with other agents.…”
Section: Resultsmentioning
confidence: 99%
“…Chemoprevention may not be possible by application of single agents and so compounds having pleiotropic actions are often recommended but studies with garlic (Allium sativum), ginkgo (Ginkgo biloba), echinacea (Echinacea purpurea), ginseng (Panax ginseng), St John' s wort (Hypericum perforatum), and kava (Piper methysticum) show undesired effects in cancer treatment. These phytochemicals interact with drug transporter P-gp, and other oxidative enzymes leading to phytokinetic alteration of commonly used chemotherapeutic drugs like cisplatin and methotrexate resulting in their low absorption and high elimination [24]. Such unfavorable drug interactions can do more evil than good in cancer patients stipulating more focus to be directed in unraveling the molecular mechanisms imparted by a phytochemical before being used in alliance with other agents.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, dose-modified GDP therapy after administration of mogamulizumab achieved an objective response. The treatment was generally well tolerated [5,7,8]. Since AITL affects relatively elderly patients (median age of 67 years) [9], GDP therapy could be useful as salvage therapy in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that significant clinical interactions are less frequently observed and reported than PK drug interactions; although, this depends on the intrinsic potency of inhibitors or inducers and if the therapeutic indices of co-administered drugs are wide [4,33,85,86]. Thus, PK drug interactions may not affect efficacy or lead to clinically evident toxic effects [82].…”
Section: Discussionmentioning
confidence: 99%
“…The potassiumsparing diuretics, such as spironolactone, can be involved in significant DDIs leading to arrhythmia or fatal hyperkalemia [66]. Diuretics were recently reported as one of the main causes of drug interaction in cancer patients [4].…”
Section: Anti-hypertensive Drugs (Supplementary Table 4)mentioning
confidence: 99%
See 1 more Smart Citation